2010
DOI: 10.1111/j.1447-0756.2009.01096.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial comparing short versus long‐term catheterization after uncomplicated vaginal prolapse surgery

Abstract: The early removal of catheter seems more advantageous, with lower incidence of urinary tract infection and a shorter hospital stay although associated with an increased risk of recatheterisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 15 publications
4
31
0
7
Order By: Relevance
“…The one self‐care trial (Hansen & Olsen, 2015) found that compared to using bedpans and urine bottles, postoperative ambulant toileting in the recovery room reduced the frequency of catheterisation but had a mixed effect on variables such as mobilisation, pain relief and nausea. The catheter care studies included three investigating immediate or early postoperative vs. delayed catheter removal (Alessandri, Mistrangelo, Lijoi, Ferrero, & Ragni, 2006; Dunn, Shlay, & Forshner, 2003; Kamilya, Seal, Mukherji, Bhattacharyya, & Hazra, 2010). Results were conflicting, with two demonstrating no between‐group differences in infection rates but one positive for early removal.…”
Section: Resultsmentioning
confidence: 99%
“…The one self‐care trial (Hansen & Olsen, 2015) found that compared to using bedpans and urine bottles, postoperative ambulant toileting in the recovery room reduced the frequency of catheterisation but had a mixed effect on variables such as mobilisation, pain relief and nausea. The catheter care studies included three investigating immediate or early postoperative vs. delayed catheter removal (Alessandri, Mistrangelo, Lijoi, Ferrero, & Ragni, 2006; Dunn, Shlay, & Forshner, 2003; Kamilya, Seal, Mukherji, Bhattacharyya, & Hazra, 2010). Results were conflicting, with two demonstrating no between‐group differences in infection rates but one positive for early removal.…”
Section: Resultsmentioning
confidence: 99%
“…Conclusión: en busca de la mejor evidencia disponible, por las intervenciones de enfermería eficientes para la prevención de infecciones del tracto urinario, se entiende que la toma de la decisión de la enfermera en el uso de dispositivos debe llevarse a cabo sobre la base de una evaluación detallada e individualizada para cada paciente. Remoção precoce de cateter é mais vantajoso, com menor incidência de infecção urinária e menor tempo de internação, embora associado à re-cateterismo (1B) 16 Avalição criteriosa do tempo de permanência do cateter para evitar substituições consecutivas e infecções (3A) 10 Há evidencias de infecção urinária?…”
Section: Resuménunclassified
“…The articles comprising this subject area are about the length of time the catheter remains in situ and its removal, use of a fixation device and the procedure of clamping of the closed system and its relation to reduction of UTI ( In surgical patients, the removal of the indwelling catheter in the first day post-surgery, compared to removal on the fourth or fifth day postoperative was associated with a lower incidence of UTI, although there was an increased risk of re-catheterization (30)(31)(32)(33)(34)(35)(36) .…”
Section: Maintenance and Removal Of The Cathetermentioning
confidence: 99%
“…It is recommended that catheter remain in place after surgery for up to 24 hours, to reduce rates of symptomatic UTI (30)(31)(32)(33)(35)(36)(37) . It is suggested that the early removal of the catheter, on the other hand, during the night in comparison to the morning, decreases the patient's stay in hospital, saving resources (37) .…”
Section: Studies Were Not Found In This Irmentioning
confidence: 99%